2022
DOI: 10.3390/cancers14051284
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic Alteration of the Cancer-Related Gene TGFBI in B Cells Infected with Epstein–Barr Virus and Exposed to Aflatoxin B1: Potential Role in Burkitt Lymphoma Development

Abstract: Burkitt lymphoma (BL) is a malignant B cell neoplasm that accounts for almost half of pediatric cancers in sub-Saharan African countries. Although the BL endemic prevalence is attributable to the combination of Epstein–Barr virus (EBV) infection with malaria and environmental carcinogens exposure, such as the food contaminant aflatoxin B1 (AFB1), the molecular determinants underlying the pathogenesis are not fully understood. Consistent with the role of epigenetic mechanisms at the interface between the genome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 77 publications
0
2
0
Order By: Relevance
“…This may allow for the development of more efficient targeted therapeutic strategies for BL. 38 Recently, extensive research on the mutational signature of EBV -neg DLBCL has been conducted. Radke et al identified the three most prominent single base substitution signatures (SBS), namely SBS9 (somatic hypermutation, SHM), SBS5 (unknown etiology), and SBS40 (unknown etiology) in EBV -neg DLBCL and central nervous system lymphoma (CNSL).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This may allow for the development of more efficient targeted therapeutic strategies for BL. 38 Recently, extensive research on the mutational signature of EBV -neg DLBCL has been conducted. Radke et al identified the three most prominent single base substitution signatures (SBS), namely SBS9 (somatic hypermutation, SHM), SBS5 (unknown etiology), and SBS40 (unknown etiology) in EBV -neg DLBCL and central nervous system lymphoma (CNSL).…”
Section: Discussionmentioning
confidence: 99%
“…explored the DNA methylation profiles associated with both eBL and AFB1 exposure, identified a shared signature affecting the expression of a putative tumor suppressor TGFBI, and revealed a B‐cell transformation mechanism shared by both EBV and AFB1. This may allow for the development of more efficient targeted therapeutic strategies for BL 38 . Recently, extensive research on the mutational signature of EBV ‐neg DLBCL has been conducted.…”
Section: Discussionmentioning
confidence: 99%
“…These changes alter chromatin exposure [12] . Like NPC, BL causes epigenetic reprogramming by silencing at least one critical transcription factor [14]. BL and NPC both have inappropriate activation of the inflammatory NFKB pathway [15, 16], causing massive immune deregulation.…”
Section: Introductionmentioning
confidence: 99%